Expressions of MMPs and TIMP-1 in Gastric Ulcers May Differentiate H. pylori-Infected from NSAID-Related Ulcers - Hsiu-Chi Cheng; Hsiao-Bai Yang; Wei-Lun Chang; Wei-Ying Chen; Yi-Chun Yeh; Bor-Shyang Sheu (The Scientific World Journal)
Background. Two major causes of gastric ulcers are Helicobacter pylori (H. pylori) infection and nonsteroidal anti-inflammatory drug (NSAID) use. Aims. This study aimed to determine if there were different expressions of matrix metalloproteinases (MMPs) and tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) between H. pylori-infected and NSAID-related ulcers. Methods. The 126 gastric ulcer patients (H. pylori infected n=46; NSAID related n=30; combined with two factors n=50) provided ulcer and nonulcer tissues for assessment of MMP-3, -7, and -9 and TIMP-1 expression by immunohistochemical staining. Results. Gastric ulcer tissues had significantly higher MMP-3, -7, and -9 and TIMP-1 expressions than nonulcer tissues (P<0.05). H. pylori-infected gastric ulcers had even higher MMP-7, MMP-9, and TIMP-1 expressions in epithelial cells than NSAID-related gastric ulcers (P<0.05). In patients with the two combined factors, gastric ulcers expressed similar proportions of antral ulcers and MMP-7 and MMP-9 intensities to NSAID-related gastric ulcers, but lower MMP-9 and TIMP-1 than H. pylori-infected gastric ulcers (P<0.05). Conclusions. H. pylori-infected gastric ulcers express higher MMP-7, MMP-9, and TIMP-1 than NSAID-related ulcers. In patients with the two combined factors, ulcer location and MMP-7 and MMP-9 intensities are similar to NSAID use.